Prostorski prikaz produkcijske sposobnosti gozdnih rastišč v Sloveniji - Bončina, Andrej (Gozdarski vestnik, 2014)
Site indices of tree species per forest sites, defined by forest communities at the forest association level were the basis for estimation of forest productivity of forest sites (PSGR) in Slovenia. The PSGR values were calculated per sub-compartments (n =54,156) considering portions of forest site types. PSGR determination for 74 forest site types and calculation of mean value of PSGR per sub-compartments included four stages: 1) assessment of %natural% tree species composition of forest site types, 2) estimation of production capacity of individual %natural% tree species in each forest site type, 3) calculation of mean value of forest site productivity at a sub-compartment level, and 4) spatial overview of calculated values of PSGR per sub-compartments for the whole forest area of Slovenia. Production capacity of the 74 forest site types varies between 0 in 22.1 m3ha-1 year-1, mean value amounted to 7.5 m3ha-1year-1. In the 77 % of the whole forest area, the PSGR amounts to 6-10 m3ha-1year-1. Algorithms used in the study enable permanent updating of the forest site productivity map. The spatial estimation of forest sites productivity in Slovenia can be improved by additional research on site indices, improved algorithms for the PSGR determination, and detailed phytosociological mapping of forest communities.
Keywords: rastiščni indeks; site index; forest site productivity; produkcijska sposobnost; forest site types; gozdni rastiščni tipi; Slovenia; Slovenija